Environmental Policies, Innovation and Productivity in the EU - Roberta De Santis; Cecilia Jona Lasinio (London School of Economics and Political Science (LSE), European Institute, 2015)
In this paper we test the weak Porter hypothesis on a sample of European economies in the period 1995-2008. We focus on the channels through which tighter environmental regulation affects productivity and innovation. Our findings suggest that the "weak" Porter hypothesis cannot be rejected and that the choice of policy instruments is not neutral. In particular, market based environmental stringency measures seem to be the most suitable to stimulate innovation and productivity growth. Consistently with the strategic reorientation of environmental policies in the European Union since the end of the eighties, our results indicate that the EU might privilege market based instruments in order to meet more effectively the 2030 targets, especially through the channels of innovation and productivity enhancement.
Keywords: D24; Q50; Q55; O47; O31; 330; environmental regulation; productivity; innovation; Porter hypothesis